Effect of grain size on high-temperature corrosion performance of laser cladding inconel 625 coating - Jiayi Peng; Kaiyang Li; Zhonghao Xie; Liming Tan; Yan Wang; Feng Liu; Yong Liu (Journal of Materials Research and Technology)
As the calorific value of waste-to-energy incineration continues to rise, the corrosion damage to boilers becomes increasingly severe. The impact of the grain size on the high-temperature corrosion resistance of Inconel 625 coating was investigated. The results indicated that the corrosion performance of the coating in 1:1 NaCl–KCl salts at 700 °C for 120 h was highly dependent on the grain size of the coating. The coating fabricated with a laser power of 1800 W and an overlapping distance of 1.5 mm had an average grain size of 13.7 μm and highest hardness, exhibiting the best corrosion performance, with a corrosion weight loss of 1.4 mg/cm2. Coatings processed under different conditions all formed a three-layered structure, with a NiO outermost layer, a Cr2O3 intermediate layer, and an innermost Cr-depletion zone. Coatings with finer grains formed a continuous and dense protective oxide layer of NiO and Cr2O3 due to the rapid diffusion of alloy elements, effectively preventing the invasion of corrosive media and protecting the substrate from corrosion.